<h3><u>(1 + 5y)(1 - 5y) is the fully factored form of this polynomial.</u></h3>
This polynomial can be factored using difference of squares.
This polynomial is in the form of a^2 - b^2 = (a + b)(a - b)
Because 1 * 1 = 1, we can use this formula to simplify this polynomial.
1 - 25y^2 = (1 + 5y)(1 - 5y)
We can use FOIL to verify this.
(1 + 5y)(1 - 5y)
1 - 5y + 5y - 25y^2
1 - 25y^2
Answer:
x=15
Because 3x15=45
Hope that helped!
:):(:(:):)(:(:$:):(:(:(:):)3():):);;
-4fx + -8f - 5
I’m pretty sure that’s correct, might be wrong double check with someone else
Answer:
the third selection is corret
Step-by-step explanation:
Ax + by + c = 0, k = - a/b.
so The slope of the first line =
,
the slope of the second line =
;
So these two lines are parallel and they don't intersect